Islam, Papuanness and Indonesianess within Papuan Muslims in Fakfak - Saidin - Ernas; Ismail DP; Ismail Kilderak (Al-Albab, 2021)
This study shows that the long historical process associated with Islam in West Papua has an impact on defining a unique identity, and significantly interrelating Islam, Papuanness and Indonesianness. The data in this study were collected for three months in Fakfak of West Papua eploying methods of observation, interview and documentation. There were some key informants being the data sources consisting of religious leaders, community leaders and government employees. Two impotrant findings are found in this work. First, the presence of Islam in Papua has significantly contributed to the formation of the identity of the Fakfak community in Papua through an intense and strong acculturation process between Islam and local Papuan culture. This process has formed new inclusive and tolerant values that are reflected in the local wisdom of satu tungku tiga batu (one stove with three stones). Second, Islam and Papuanness in Fakfak appear to have certain implications on the formation of Indonesian (national) identity. Theoretically, this research shows that identity is not something fixed and natural, but a process that is constantly changing, with regard to the socio-political dynamics that affect it. That is why Papuan Muslims strive to continue to define themselves amid the construction of Papuan identity which is often defined as Christian and Melanesian.